Neuromyelitis optica spectrum disorders and pregnancy: therapeutic considerations - Mao-Draayer, Yang; Thiel, Sandra; Mills, Elizabeth A.; Chitnis, Tanuja; Fabian, Michelle; Sand, Ilana Katz; Leite, M. Isabel; Jarius, Sven; Hellwig, Kerstin (Nature reviews. Neurology, 2020)
Neuromyelitis optica spectrum disorders (NMOSD) are a type of neurological autoimmune disease characterized by attacks of CNS inflammation. In this Review, the authors discuss the relationship between pregnancy outcomes and NMOSD disease activity, and outline potential treatment approaches.